Pengembangan Modul Pembelajaran Multimedia untuk Meningkatkan Minat dan Pemahaman Konsep Mahasiswa Prodi Pendidikan Informatika - Yosi Nur Kholisho (Jurnal Pendidikan Informatika (EDUMATIC), 2017)
The purpose of this research is to develop and produce product in the form of multimedia instructional subjects for students on informatics education course and to know the effectiveness of modules developed based on responses of student interest to learning and learning outcomes. The method used in this research is Research and Development. Based on data from media and product expert validation, it can be seen that the product in the form of multimedia learning module for students can be categorized as "good" (37.38 X â‰¤ 46.14) with total score 45 and in terms of display can be categorized "good" (51 x â‰¤ 63) with a total score of 56. Result of student interest analysis to learning module got result that 35 person from 45 stated that more interest to learn by using module with percentage equal to 77,8%, this proves that student interest in studying material by using good module. The results obtained for the learning outcomes, the results obtained that the value before the given module 78.7 and the value after the given module 87.6 this result shows that the value of learning results after the module is given higher than with the before given the module.